Ameliorating effect of kisspeptin-10 on methotrexate-induced sperm damages and testicular oxidative stress in rats - Guvenc, Mehmet; Aksakal, Mesut (Wiley, 2018)
The purpose of this study was to determine the kisspeptin-10 (Kiss) administration on the damages in testicular oxidant-antioxidant system, reproductive organ weights and some spermatological characteristics resulted from methotrexate (MTX) exposure. Group 1 (n:6) received saline only; group 2 (n:6) received 50 nmol/kg kisspeptin-10 for 10 days; group 3 (n:10) received single-dose methotrexate 20 mg/kg; and group 4 (n:10) received MTX 20 mg/kg single dose and, after 3 days, received kisspeptin-10, 50 nmol/kg, lasted for 10 days by intraperitoneal injection. At the end of the study, malondialdehyde levels were found to have increased following the application of MTX while showing a significant reduction in group 4 with Kiss administration. With respect to the spermatological parameters, administering MTX decreased motility and increased the rates of abnormal spermatozoa in group 2, while improvements were observed in group 4 in the form of increased motility in the spermatozoa and fewer abnormal spermatozoa. In addition, Kiss treatment provided statistically significant increases in the absolute weight of the seminal vesicles and the relative weights of the right cauda epididymis and seminal vesicles resulting from MIX administration. MTX administration damaged some spermatological parameters and increased oxidative stress when compared to the control group. However, Kiss treatment was observed to mitigate these adverse effects as demonstrated by the improvements in coadministration of Kiss and MTX when compared to the MTX group. It is concluded that Kiss treatment may reduce MTX-induced reproductive toxicity as a potential antioxidant compound.
Keywords: kisspeptin; methotrexate; oxidative stress; sperm quality